2011
DOI: 10.1007/s10195-011-0129-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic management of complicated talar extrusion: literature review and case report

Abstract: Total extrusion of the talus with interruption of all ligaments (missing talus) is a rare injury. We describe the case of a 27-year-old man who reported total extrusion of the talus after a motorbike accident with interruption of all talar ligaments. In the first repair effort, the articular void left by the talus was filled with antibiotic cement and the wound was closed primarily. Nevertheless, the skin overlying the talar joint displayed necrosis. In order to cover the cutaneous defect, improve local vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
21
0
2
Order By: Relevance
“…The total extrusion was treated initially with cement spacer and distally based sural fasciocutaneous flap, followed by delayed reimplantation and arthrodesis after confirming the negative cultures of the original talus. They suggested that the flap might have promoted revascularization, which ultimately avoided the avascular necrosis of the reimplanted talus [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total extrusion was treated initially with cement spacer and distally based sural fasciocutaneous flap, followed by delayed reimplantation and arthrodesis after confirming the negative cultures of the original talus. They suggested that the flap might have promoted revascularization, which ultimately avoided the avascular necrosis of the reimplanted talus [4].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the treatment choice, when facing an open pantalar dislocation, commonly accompanied by an anterolateral wound of the ankle, early surgical debridement is the most important initial step [2][3][4][5][6][7][8][9]. The use of an external fixator to stabilize the joint while waiting for definitive treatment could also decrease wound complications and allow proper wound care [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Open reduction has resulted in frequent complications like avascular necrosis and osteomyelitis affecting 38-85.7% of cases [4,18,19]. Delayed intervention leads to skin necrosis requiring sural fasciocutaneous island flap [20]. There is no evidence-based strategy in the management of TTD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functional outcomes of patients managed by primary talectomy were worse than those of the group as a whole, none of the former cases achieving a good outcome. Many of the reviewed articles recommended attempting to preserve the talus, even in cases of total extrusion with significant contamination, preservation having a better chance for a good outcome and a similar risk of complications 3,[31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%